The Importance Of Commitment To The Young People In Service To The Foundation Of The Love Of The Poor, Surabaya - Saefnat Saetban (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
The phenomenon of the commitment of young people should be the object of attention for the church-the church or the Christian Foundations in developing their potential, As about the presence of young people the future of the church will be much better. Researchers have conducted preliminary observations and interviewed one of them. The information submitted is true that they have a longing to immerse themselves in the service to the maximum just haven't gained the trust of the management of the church.